Genetic Characteristics of the Rat Fibroblast Cell Line Rat-1 - Thomas Liehr; Stefanie Kankel; Eva Miriam Buhl; Sarah K. Schröder-Lange; Ralf Weiskirchen (Cells)
The Rat-1 cell line was established as a subclone of the parental rat fibroblastoid line F2408, derived from Fisher 344 rat embryos. Rat-1 cells are widely used in various research fields, especially in cancer biology, to study the effects of oncogenes on cell proliferation. They are also crucial for investigating signal transduction pathways and play a key role in drug testing and pharmacological studies due to their rapid proliferation. Therefore, Rat-1 cells are an indispensable research tool. While some cytogenetic information on their basic chromosomal features is available, detailed genomic analyses, such as karyotype analysis, short tandem repeat (STR) profiling, and whole-genome sequencing, have not been thoroughly conducted. As a result, the genetic stability and potential variations in Rat-1 cells over extended culture periods are poorly understood. This lack of comprehensive genetic characterization can limit the interpretation of experimental results and requires caution when generalizing findings from studies using this cell line. In this study, we describe the genetic characterization of the Rat-1 cell line. We established a karyotype, performed multicolor fluorescence in situ hybridization (mFISH), identified chromosomal losses and gains, and defined an STR profile for Rat-1 with 31 species-specific markers. Interestingly, the chromosomal imbalances found in Rat-1 cells resemble those found in human epithelioid sarcoma or liposarcoma. Additionally, we analyzed the transcriptome of Rat-1 cells through mRNA sequencing (mRNA-Seq) using next-generation sequencing (NGS). Finally, typical features of these fibroblastic cells were determined using electron microscopy, Western blotting, and fluorescent phalloidin conjugates.